A comparative study of verbal particles in varieties of Vend Romani. Issue 2 (December 2015) - BODNÁROVÁ, ZUZANA; WIEDNER, JAKOB
Abstract : Vend Romani is a Romani dialect spoken in the adjacent regions of Transdanubia (Hungary), Burgenland (Austria) and Prekmurje (Slovenia). Through intensive contact with German and Hungarian, Vend Romani developed the category of verbal particle; these particles are used to derive new verbs or assign certain aktionsart s to verbs. This study focusses on two varieties spoken in Hungary, in the counties of Zala and Somogy, while the varieties of Burgenland and Prekmurje are consulted for comparison. Since the verbal particles of Zala and Somogy display significant differences, they will be initially described in terms of their development, position, function and productivity. It will be shown that verbal particles may follow various paths of development, one of which is related to the change of contact languages. Based on the examined varieties' set of verbal particles, we will distinguish two Vend Romani subgroups: Somogy–Burgenland and Zala–Prekmurje.